FDA approves revised prescribing for clozapine; new REMS in effect. Issue 12 (December 2015) - Farchione, Tiffany R.
Abstract : EDITOR'S NOTE: We don't usually publish contributions from outside our own staff. However, at the request of the Food and Drug Administration, and given the importance of the topic, we've made an exception for the following article on changes in prescribing procedures for clozapine .